Workshop Penulisan Karya Ilmiah Bagi Mahasiswa - Agus Sutriawan; Irvan Irvan; Muhammad Akbar Syafruddin; M Imran Hasanuddin; Ikadarny Ikadarny; Sufitriyono Sufitriyono; Retno Farhana Nurulita (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2023)
The methodology for this activity includes providing instructions, support, and publication of research results for students of the Physical Education, Health, and Recreation Study Program, Faculty of Sports Science, Makassar State University. In order to develop writing skills and prepare students to write and share their scientific work, students are encouraged to write articles and publish research results during the final semester. Based on these findings and analysis, it can be said that students have a fairly high level of enthusiasm in producing scientific work. Their initial understanding of scientific writing and writing techniques is lacking. Therefore, to improve students' knowledge and skills in writing scientific papers, they must take part in this exercise. The participants' understanding and writing ability increased. The results of these efforts show how useful this training activity is in helping students become more knowledgeable and proficient in writing scientific papers. Writing scientific articles can be used as ongoing training. In addition, various writing tools for current scientific references are accessible. Because the Mandeley software usage instructions for reference are needed to improve writing